Demystifying China’s Impacts on the Iron Ore Market: A VECM Approach - Huang, Ying (2016)
This paper analyzed China’s impacts on the iron ore market using the Vector Error Correction Model (VECM). The significant statistical results indicate that world GDP, China GDP, China’s total Fixed Asset Investment (FAI), real estate investment and FAI on transportation are useful in predicting the iron ore price. Additionally, the impulse and response analysis suggests that shocks to China’s real estate investment and FAI have significant and permanent impacts on the iron ore price. In contrast, shocks to other variables have no long-term effects. Lastly, based on the model, we predict that iron ore will rally in the two quarters of 2016.